Indigenous Student Success in Public Schools: A “We” Approach for Educators - Moon, Martha; Berger, Paul (Alberta Journal of Educational Research, 2016)
What does Indigenous student success look like in public school boards? Seven urban Indigenous educators’ interview responses to this question were interpreted and reported by the lead author, a teacher and researcher of English, Irish, and Scottish heritage—a Settler Canadian. The “Connected Beads Model” is the result of these educator-to-educator interviews. It shows how Indigenous students’ success can be promoted when Settler and Indigenous educators take a “We” stance alongside students, families, and communities through honoring story, relationship, and holism in school. The concepts embedded in the model and its practical applications are explored through participants’ quotations and considered alongside related literature on Indigenous education. À quoi ressemble la réussite des élèves autochtones dans les conseils scolaires publics ? Les réponses en entrevues des sept éducateurs autochtones en milieu urbain ont été interprétées et dévoilées par l’auteur principal, un enseignant et chercheur d’origine anglaise, irlandaise et écossaise—un Canadien « de souche ». De ces entrevues entre enseignants découle le modèle dit des « perles liées » qui démontre l’effet positif sur la réussite des élèves autochtones qui se crée lorsque les éducateurs « canadiens de souche » et les éducateurs autochtones adoptent une attitude de solidarité avec les élèves, les familles et les communautés et qu’ils rendent hommage aux récits, aux relations et à l’holisme à l’école. Les concepts incorporés au modèle et les applications pratiques de celui-ci sont explorés par le biais des commentaires des participants et dans le contexte de la littérature connexe portant sur l’éducation autochtone.